The realising of religion moderation in Tareqa Al-Yusriyyah As-Siddiqiyyah Ash-Shadhiliyyah - Khotimah, Khusnul (HTS teologiese studies, 2023)
This study aims to clarify certain ideas regarding Al-Yusriyyah Ash-Shdhiliyyah Siddqiyyah Tariqa and its function in religious moderation. Tareqa can be a new formula in realising harmony in religious diversity, in which the teaching principle of Tariqa is the spirit of improving moral and character. This is very important in living in diversity. By implementing Tariqa, a person understands religion not only from the outward side but also from the inner part of religion, so that it is expected to be able to find the substance, namely, the true truth that is universal. From this point of view, the Sufism paradigm seems to have advantages that the person is more tolerant of differences, both internal and external. A field study was conducted to achieve the objective of this research. Particularly, this study used an interdisciplinary approach, that is, a combination of religious and social approaches. A participatory observation, deep interviews and documentations were employed to collect the data of this study. The subjects of this research were adherents of the Tariqa in Cairo, Egypt and Indonesia. This study reveals that Tariqa has teachings and values in realising religious moderation in a plural society. This Tariqa could be an agency of religious moderation. The significance of this study is to prove the power of Tariqa and Sufism as agents of change in plural societies against extremist and intolerable attitudes both between devotees of particular religions and between adherents of different religions. Accordingly, it can promote a peaceful and tolerant way of life and reduce violence. This study supports earlier research that suggested Sufism as an option for governmental action in a plural society to counteract radicalism and intolerance.Contributions: The results of this study are expected to contribute to providing suggestions to the stakeholders in dealing with the rise of religious intolerance and radicalism both globally and locally. Moreover, the ritual, doctrinal and social interaction of Tareqa Al-Yusriyyah As-Siddiqiyyah Ash-Shadhiliyyah can be a source of reference and inspiration for the policy of stakeholders in deradicalising religion and creating religious moderation.